Expression of soluble triggering receptor expressed on myeloid cells‐1 in childhood CF and non‐CF bronchiectasis. Issue 4 (27th October 2014) - Masekela, R.; Anderson, R.; de Boeck, K.; Vreys, M.; Steel, H.C.; Olurunju, S.; Green, R.J.
Summary: Background: Soluble triggering receptor expressed on myeloid cells‐1 (sTREM‐1) is demonstrating promise as an inflammatory biomarker of acute infection in various pulmonary conditions; including community acquired pneumonia, ventilator associated pneumonia and non‐tuberculous mycobacterial infection. Introduction: The expression of sTREM‐1 has been poorly studied in all forms of bronchiectasis, both in the context of cystic fibrosis (CF) and non‐cystic fibrosis bronchiectasis. Method: : Induced sputum samples were collected for sTREM‐1 determination in children with HIV‐associated bronchiectasis and CF‐bronchiectasis. The presence or absence of an exacerbation was noted at study entry. Lung function parameters (FEV1, FVC, FEV1 /FVC, FEF25–75 ) were measured using the Viasys SpiroPro Jaeger Spirometer (Hoechberg, Germany). Result: : A total of twenty‐six children with HIV‐associated bronchiectasis and seventeen with CF were included. With respect to sTREM‐1, the levels were readily detected in both groups, but were significantly higher in children with HIV‐associated bronchiectasis (1244.0 pg/ml (iqr 194.5; 3755.3 pg/ml) and 204.9  pg/ml (iqr 66.9; 653.6 pg/ml) P  = 0.003. There was a positive correlation between sTREM‐1 and IL‐8 as well as sputum neutrophil elastase in the HIV‐bronchiectasis group (r = 0.715 and r = 0.630), respectively both P  < 0.005. sTREM‐1 was not further increased in subjects presenting with an acute pulmonary exacerbation in the HIV‐associated bronchiectasis and in CF participants ( P  = 0.971 and P  = 0.481), respectively. In the CF group sTREM‐1 strongly correlated with FVC% predicted and FEV1 % predicted (r = 0.950 and r = 0.954), both P  < 0.005. Conclusion: The pulmonary innate immune functions are over‐active in HIV‐associated bronchiectasis, with readily detected sTREM‐1 values, which were higher than those in CF. sTREM‐1 does not correlate with markers of HIV‐disease activity but does correlate with markers of neutrophilic inflammation. In CF sTREM‐1 has a negative correlation with pulmonary function parameters.Pediatr Pulmonol. 2015; 50:333–339. © 2014 Wiley Periodicals, Inc.